The labor market in Austria, 2000-2016 - René Böheim (IZA World of Labor, 2017)
Austria is an interesting economy due to its strong industrial relations with institutionalized collective bargaining over wage negotiations and working conditions. Currently, Austria's GDP per capita is high, but unemployment, although comparably low on an international scale, is not declining in the aftermath of the financial crisis. The labor market is also characterized by an increasing share of mostly low-skilled foreign workers. High marginal labor taxes discourage low-skilled workers from leaving social assistance.
Keywords: 330; wages; unemployment; Austria